1996
DOI: 10.1002/j.1556-6978.1996.tb00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Client Perceptions of Counselors‐In‐Training: The Effects of Sex and Gender Role Orientation

Abstract: The effects of the sex of the counselor and of gender role orientation on client ratings of counselors‐in‐training were examined. An interaction between sex and gender role orientation was found for differences in clients' willingness to refer a friend to the counselor. Implications for training and research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…Similar to previous research (e.g. Ametrano & Pappas, 1996;Gross, 2006;Kivlighan, 1989Kivlighan, , 1990Kivlighan & Shaughnessy, 2000;Stiles et al, 2002;Stiles & Snow, 1984), differences in session rating are expected between counsellors-intraining and their clients adding further clarity to the training issues related to counsellors-in-training.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Similar to previous research (e.g. Ametrano & Pappas, 1996;Gross, 2006;Kivlighan, 1989Kivlighan, , 1990Kivlighan & Shaughnessy, 2000;Stiles et al, 2002;Stiles & Snow, 1984), differences in session rating are expected between counsellors-intraining and their clients adding further clarity to the training issues related to counsellors-in-training.…”
supporting
confidence: 50%
“…Ametrano & Pappas, 1996;Dunn, Borgers, & Thomas, 1988;Gross, 2006;Kivlighan, 1989Kivlighan, , 1990Kivlighan & Shaughnessy, 2000;Lent et al, 2006;Stiles & Snow, 1984;Stiles, Gordon, & Lani, 2002) that have explored counsellors-in-training perceptions, session ratings by clients and novice counsellors, and other factors related to in-session ratings and session outcomes. Ametrano and Pappas (1996), for example, explored the effects of sex and gender role orientation of novice counsellors on session outcomes. It was found that gender role orientation and the sex of the counsellor alone did not affect client perception of session quality, but that both variables together did affect session quality perception.…”
mentioning
confidence: 96%
“…Despite the cautions that Spence and others (e.g., Good, Borst, & Wallace, 1994) have voiced regarding what is being measured by both the PAQ and the BSRI (i.e., instrumentality and expressiveness), it is common for researchers to discuss their use of both instruments as measures of global masculinity and femininity. Furthermore, despite Spence's (1993) attempts to clarify the focus of the PAQ scales by beginning to refer H o f f m a n to the Feminine scale as Expressive (E) and the Masculine scale as Instrumental (I), it is common for scholars to prefer the original scale descriptors (i.e., Masculine and Feminine), even while acknowledging Spence's change in nomenclature, as exemplified by Ametrano and Pappas (1996): "In her recent writings, Spence (1993) referred to the Instrumental (I) and the Expressive (E) scales . .…”
Section: The Personal Attributes Questionnaire (Paq)mentioning
confidence: 99%
“…Several studies in the counseling literature have addressed such issues as gender role orientation and its role in the counseling relationship (Ametrano & Pappas, 1996;Seem & Johnson, 1998), gender role perspectives of counselors and clients (Hoffman, 2006a(Hoffman, , 2006bHoffman, Hattie, & Borders, 2005), and sex and gender in counselor supervision (e.g., Seem & Johnson, 1998). Also of note are the career development, experience, and performance of counselor educators with respect to gender.…”
Section: Leadership Challengesmentioning
confidence: 99%